2018
DOI: 10.3389/fendo.2018.00524
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes Derived From Mesenchymal Stromal Cells Pretreated With Advanced Glycation End Product-Bovine Serum Albumin Inhibit Calcification of Vascular Smooth Muscle Cells

Abstract: Background: The osteogenic differentiation of vascular smooth muscle cell (VSMCs) is important for the development of vascular calcification (VC), particularly in diabetes. Exosomes derived from Mesenchymal Stromal Cells (MSCs) are effective against cardiovascular diseases, yet their role in VC remains unclear. Advanced glycation end products (AGEs) inhibit bone marrow stromal cell osteogenesis by targeting osteogenesis-associated genes. Thus, we investigated the role of exosomes derived from MSCs pretreated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 63 publications
0
26
1
Order By: Relevance
“…In contrast, the miRNAs enriched in the lean‐EVs mainly targeted the Rho family of GTPases and ephrinA‐EphA. More recently, Wang et al reported that compared with exosomes derived from normal BMSCs, exosomes derived from AGE‐BSA‐pretreated BMSCs showed increased expression of miR‐146a and exhibited a more potent inhibitory effect on vascular smooth muscle cell calcification . In the present study, we found that the expression levels of some downstream genes of target cells, including Col1 , Runx2 , and VEGFA , were different between the dBMSC‐exos and nBMSC‐exos treatment groups.…”
Section: Discussioncontrasting
confidence: 51%
“…In contrast, the miRNAs enriched in the lean‐EVs mainly targeted the Rho family of GTPases and ephrinA‐EphA. More recently, Wang et al reported that compared with exosomes derived from normal BMSCs, exosomes derived from AGE‐BSA‐pretreated BMSCs showed increased expression of miR‐146a and exhibited a more potent inhibitory effect on vascular smooth muscle cell calcification . In the present study, we found that the expression levels of some downstream genes of target cells, including Col1 , Runx2 , and VEGFA , were different between the dBMSC‐exos and nBMSC‐exos treatment groups.…”
Section: Discussioncontrasting
confidence: 51%
“…All the animal procedures were approved by the Institutional Animal Care and Use Committee of Tongji Medical College, Huazhong University of Science and Technology (IACUC number TJ-A20161208). Rat BMSCs were isolated, cultured, and characterized as described in previous study (Wang Y. et al, 2018). Following euthanasia, the femur and tibia of SD rats were obtained and bone marrow was flushed out with Dulbecco’s modified Eagle’s medium (DMEM)/F12 with 10% fetal bovine serum (FBS).…”
Section: Methodsmentioning
confidence: 99%
“…PKH67 green fluorescent cell linker kit (Sigma-Aldrich) was used to label the tMSC cell membrane as well as tMSC-derived exosomes [28,29,30], according to the manufacturer’s recommendations. In brief, tMSC cells or isolated exosome from tMSC conditioned medium were placed in conical bottom polypropylene tube and wash once using serum-free medium.…”
Section: Methodsmentioning
confidence: 99%